A comparative study of legitimation strategies in hybrid regimes. (3rd July 2016) - Mazepus, Honorata; Veenendaal, Wouter; McCarthy-Jones, Anthea; Trak Vásquez, Juan Manuel
ABSTRACT: Despite the growing body of research on 'hybrid regimes', few studies address the issue of their domestic legitimacy. Targeting this gap in the literature, this article explores the legitimation strategies of three hybrid regimes around the globe: Russia, Venezuela, and Seychelles. Although these countries differ markedly in almost every aspect that can be thought of, the political systems of all three cases combine formally democratic institutions with authoritarian political dynamics. The qualitative, comparative analysis presented in this article uncovers a number of remarkable similarities between the regimes' respective legitimization strategies. However, while the strategies for engendering legitimacy are similar across the cases, the content of these strategies is different: the Russian leadership mainly relies on preserving order and nationalism, the Venezuelan regime employs a more populist strategy, and the Seychellois regime uses a more personal and particularistic approach. Our findings not only provide insights into the mechanisms hybrid regimes use to consolidate their authority, but also highlight important differences and similarities between hybrid regimes around the world.